2018
DOI: 10.1051/e3sconf/20186000038
|View full text |Cite
|
Sign up to set email alerts
|

Physical simulation of integrated protective structures

Abstract: An effective way of protecting development workings by integrated rock wall structures is considered. The necessity of improving this method and its experimental verification is substantiated. Integrated rock wall structures are experimentally tested under laboratory conditions. On the basis of the results of physical modeling, parameters of integrated structures have been specified in terms of impact factors; their yield strength is also specified. The condition for ensuring the stability of the integrated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Instrumental observations in the ventilation raise have demonstrated that within mine workings, supported in front of the longwall, period of intensive shifts correlated with the period when the mine working gets to abutment pressure area. That coincides with common idea of deformation processes within mine workings being supported in a zone of longwall affect (Ma et al, 2018a;Ma et al, 2018b;Nehrii, Nehrii, & Piskurska, 2018). It is possible to determine general characteristic of the mine working deformation while analyzing its height variations depending upon distance to the longwall (Fig.…”
Section: Resultssupporting
confidence: 78%
“…Instrumental observations in the ventilation raise have demonstrated that within mine workings, supported in front of the longwall, period of intensive shifts correlated with the period when the mine working gets to abutment pressure area. That coincides with common idea of deformation processes within mine workings being supported in a zone of longwall affect (Ma et al, 2018a;Ma et al, 2018b;Nehrii, Nehrii, & Piskurska, 2018). It is possible to determine general characteristic of the mine working deformation while analyzing its height variations depending upon distance to the longwall (Fig.…”
Section: Resultssupporting
confidence: 78%
“…These allow solving geomechanical problems with a wide array of parameters very quickly. The following packages are the most popular: ANSYS [12 -14], Solid Works [14], PLAXIS [11, 15 -19], FLAC3D [20 -22] and PHASE-2 [23 -25]. These software systems give almost identical results [30] but differ in the degree of complexity in constructing the model's geometry and in using different models of material behaviour when setting tasks.…”
Section: Main Partmentioning
confidence: 99%
“…Hence, potential energy of roof deformation for calculation alternatives, represented in Figure 1 and 2, is accumulated similarly in terms of the quantitative index. Through the changes in the value and geometry of vertical stress gradient, taking place in the process of complete backfilling, distance between the main cracks increases relative to packs resulting in the formation of larger rock blocks (Sotskov, Russkikh, & Astafiev, 2015;Nehrii, Nehrii, & Piskurska, 2018).…”
Section: Effect Of Technological Parameters Of Packs and Complete Backfillingmentioning
confidence: 99%